Training of Tax Implementation for Micro, Small, and Medium Enterprises in the Digitalization Era - Susanna Hartanto (Faculty of Smart Technology and Engineering, Universitas Kristen Maranatha, Bandung, Indonesia, 2024)
Training in tax implementation aims to improve knowledge and understanding of taxation for small and medium enterprises in the current digital era. This activity was motivated by the condition where many small and medium enterprises in the East Java I Regional Office of the Directorate General of Taxes still did not understand and did not apply the latest tax regulations correctly and completely according to Regulation of the Minister of Finance Regulation No. 164 of 2023 concerning the procedure for imposing income tax on income from businesses received or obtained by taxpayers who have a certain gross income and obligation to report businesses to be confirmed as taxable entrepreneurs. Training activity was carried out using an online method and training materials were given to participants in the form of digital presentation files and spreadsheet files. Methods used in implementing this activity consist of preparation, implementation, and evaluation. Pre-tests and post-tests were carried out to determine the increase in knowledge and understanding of webinar participants. Overall, taxpayers who are from the small and medium enterprises feel helped in gaining knowledge and understanding the latest tax regulations and can apply the latest regulations in filling out the annual tax return form so that they can report the annual tax return correctly and completely.